Patterning of Gold Nanoparticles on DNA Self-Assembled Scaffolds. (11th February 2008) - Cheng, Immensee; Wei, Bryan; Zhang, Xunyun; Wang, Yongjian; Mi, Yongli
Abstract : We report a method of patterning the 1D and 2D arrays of gold nanoparticles on the DNA self-assembled scaffolds. The 5 nm gold nanoparticle was well positioned at the center of each 4 × 4 tile motif of the DNA scaffold. The precisely located gold particles can form 1D and 2D arrays. This controllable scaffolding technology may become a promising tool for nanoscaled fabrication of electronics and photonic devices.